Identification Of Bacteria In Seaweed (Kappaphycus alvaezii) Infected With Ice-Ice Disease In Tarakan City: Bahasa Indonesia - Burhanuddin Ihsan; Kartina Kartina; Rully Fadliansyah (University of Prof. Dr. Hazairin, SH, 2022)
Seaweed (Kappaphycus alvarezii) is a fishery product that has enormous potential as well as has high economic value with very diverse processed products that can improve the welfare of coastal communities. However, the problem that often arises in seaweed cultivation is the presence of ice-ice disease. Symptoms of ice-ice disease are generally characterized by bleaching at the base of the thallus, middle and tip, which begins with a change in color of the thallus to clear white or transparent. This study aimed to analyze the pathogenic bacteria in seaweed (K. alvarezii) which was attacked by ice-ice disease in Tarakan City. Bacterial isolation was carried out by smoothing 30 grams of seaweed samples that had been taken and then 5 grams of it put into an Erlenmeyer containing 250 ml of APW enrichment media and then incubated for 6-8 hours at 370C. Furthermore, the sterilized spherical needle was inserted into the APW medium and then streaked on TCBS and 3% TSA media using the streak plate method and incubated at 370C for 24 hours. Then the bacterial colonies that grew on the media were selected with different colors, shapes and elevations to be purified. Identification of bacteria using the Manual for the Identification of Medical Bacteria and Bergey's Manual of Determinative Bacteriology based on morphological and biochemical characteristics. The results of the study by identifying bacteria in seaweed that were attacked by ice-ice disease based on morphological and biochemical tests found the infecting bacteria were Actinobacillus, Moraxella, Alcaligenes, Vibrio and Bacillus. In conclusion, there were 5 pathogenic bacteria identified in seaweed that was attacked by ice-ice disease including; Actinobacillus, Moraxella, Alcaligenes, Vibrio and Bacillus